Eco-Drainage Combined with Infiltration Wells for Sustainable Flood Control - Belladona, Meilani; Gunawan, Reto Indra; Wardhani, Fenty Wisnu; Surapati, Alex (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2024)
Rawa Makmur is located in Muara Bangka Hulu District, Bengkulu City, with an area of 150 hectares and a population of 1,468 people. This area in the form of a swamp has experienced a 30% change in the shape of the land in a period of 3 years and causes flooding during the rainy season. The existing drainage system is unable to accommodate and drain the river. This problem requires planning an environmentally friendly drainage system design (eco-drainage), one of which is using infiltration wells. This study aims to overcome stagnant water in Rawa Makmur Village by implementing an environmentally oriented drainage system (eco-drainage) using infiltration wells. The data used are primary data (measurement of canal dimensions) and secondary data in the form of rainfall data, topographic surveys, soil testing and other supporting data which are processed using hydrological analysis and hydraulic analysis. Based on the results of data processing and analysis, it was found that the intensity of rainfall with a return period of 10 years was 11.25 mm/hour and the planned flood discharge was 0.1039 m3/s. The calculation results are used to design environmentally sound drainage using infiltration wells. The results of the analysis obtained specifications for the depth of infiltration wells of 1.50 m, a diameter of 0.5 m, the distance between infiltration wells is 50 m. The planned eco-drainage can accommodate 0.2943 m3 and can delay water runoff for 3.5846 minutes before seeping into the ground.